Metode Berkomunikasi menggunakan Sandi Hellen Keller terhadap Siswa-Siswi Tunarungu dan Tunawicara di Sekolah Luar Biasa Yayasan Tri Dharma Di Kota Cilegon - Dewi, Lina Marliana (Universitas Mathla'ul Anwar Banten, 2019)
This study aims to find out the method of communicating using the password of the hell keller against students with hearing impairment and speech at the tri dharma foundation special school in the city of Cilegon, while the method used Descriptive Method is a method that is done by collecting all the data in the research location. Then describe the data collected as information. The purpose of the study, the purpose of the study is to understand the purpose of communication, to know about the code of the hell keller Knowing the history of special schools, Understanding the meaning of deaf and speech impaired, Knowing the education system and providing guidance services to deaf and speechless students at the Tri Dharma Foundation.